Internet of Things Smart Farming untuk Monitoring Tanaman Hidroponik - Anwar , Rian Septian; Agustina , Nani; Sutinah, Entin (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Currently the cultivation of plants by means of hydroponics is partly a hobby and some are a necessity. The cultivation of hydroponic plants requires a touch of technology such as the Internet of Things (IoT). This technology is very important in order to get crop yields that have good quality and quantity. The Riyadusalihin Islamic Boarding School currently implements plant cultivation by applying hydroponics, because the activities at the Islamic boarding school are quite dense so that in farming they rely on estimates to regulate the temperature and humidity of the air resulting in failure in hydroponic farming such as vegetables not growing well, lack of quality of the plants vegetables and many vegetables wither and eventually die. The purpose of using IoT in smart farming is one of them in the cultivation of vegetable plants so that they can monitor plants without disturbing the activities of the students and can be controlled remotely so that they can condition or stabilize the temperature and humidity of the air in plants. In this study applying IoT technology using the Blynk application, where this application is one of the advances in information technology which is quite popular among smart phone users because the user interface is quite simple, many features are presented by Blynk and easy to access, with the operating system controlled. with Arduino Nano via ESP 8266 and temperature sensor DS18b20 so that monitoring of plants can be done easily and the plants will grow well by having good quality and quantity and the students can get good nutrition which can be obtained from foods such as these vegetables.